E-COMMERCE ON THE STUDY OF MASLAHAH MURSALAH (A REVIEW FROM AN ISLAMIC ECONOMIC PERSPECTIVE) - Hassan Shakeel Shah; Adib Susilo (IAIN Manado, 2022)
Currently, technological developments have provided significant changes in world economic activities and transactions. As a Muslim community that follows Islamic Shari'a, they must have adequate comprehension of the latest forms of transactions so that the economic activities carried out do not conflict with Islamic economic principles. The purpose of this paper is to describe maslahah mursalah, electronic commerce (e-commerce), and how the function of e-commerce is related to maslahah mursalah. Through qualitative research methods with descriptive analysis, this paper describes e-commerce in the study of maslahah mursalah. The results of this paper's discussion reveal that The mechanism of e-commerce has similarities with the as-salam contract in the perspective of Islamic economics. Thus, an E-commerce transaction is a form of Maslahah (providing benefits/convenience) whose level is at Maslahah Hajiyyat in terms of muamalah activities that include the sale and purchase of bai’ as-salam. Thus, the conclusion is that e-commerce has incorporated the requirements of use maslahah al-mursalah.